The aftermath of terrorism: posttraumatic stress and functional impairment after the 2011 Oslo bombing - Solberg, Øivind; Blix, Ines; Heir, Trond (Frontiers in Psychology, 2015)
Objective. In the present study we wanted to investigate the link between exposure, posttraumatic stress symptomatology and functional impairment in the aftermath of terrorism. Method. Posttraumatic stress symptomatology and functional impairment related to the Oslo bombing 22nd of July, 2011, in directly and indirectly exposed individuals (N= 1927) were assessed together with demographics, exposure, peri-traumatic reactions and event centrality approximately 1 year after the attack. Results. Directly and indirectly exposed individuals qualifying for posttraumatic stress disorder (PTSD) reported similar peri-traumatic reactions, event centrality and functional impairment. However, clusters within the PTSD symptomatology were differentially associated with impairment as a function of their exposure. In the directly exposed group, all clusters within the PTSD symptomatology were associated with impairment in function, while only emotional numbing was associated with impairment within the indirectly exposed group. Conclusions. Considering that terror attacks frequently involve directly exposed individuals and a larger population of indirectly exposed individuals, this finding is of importance, especially in the design of intervention programs and the development of treatment policies.